Peripartum outcomes and immune responses after SARS-CoV-2 infection in the third trimester of pregnancy - Qi Shen; Shuai Dong; Neelam Kumari Shah; Yuan Liang; Jie Wang; Yan-Hong Shan; Jin He (BMC, 2024)
Abstract Background SARS-CoV-2 infection in pregnant women during the third trimester resulted in overall adverse pregnancy outcomes compared to non-infected controls and a unique humoral and cellular response at delivery. In this study we aimed to assess the impact of SARS-CoV-2 infection on maternal/neonatal peripartum outcomes andimmunological profiles. Method In this study, we recruited 304 SARS-CoV-2 infected pregnant women and 910 SARS-CoV-2 non-infected pregnant women who were admitted for delivery. Peripartum and neonates' outcomes response to SARS-CoV-2 infection were analyzed. Furthermore, we characterized the antibody and cytokines profile in SARS-CoV-2 infected maternal blood (MB) and cord blood (CB). We also assessed routine laboratory tests and liver function tests in MB before labor. Unpaired T test, Mann-Whitney test and Spearman test were used to analyze the data. Results SARS-CoV-2 infected pregnant women were significantly associated with increased risk of adverse pregnancy outcomes, including preterm labor (13.8% vs. 9.5%, p = 0.033) and meconium-stained amniotic fluid (8.9% vs. 5.5%, p = 0.039). The risk of low birth weight (< 2500 g) (10.5% vs. 6.5%, p = 0.021) and Apgar score < 8 at 1-minute (9.2% vs. 5.8%, p = 0.049) significantly increased in newborns from COVID-19 positive mothers than their counterparts. Our results showed that antibodies were increased in adverse-outcome SARS-CoV-2 infected mothers and their neonates, and abnormal proportion of immune cells were detected in SARS-CoV-2 infected mothers. While the immune response showed no difference between adverse-outcome infected pregnant women and normal-outcome infected pregnant women. Thus, SARS-CoV-2 infection during the third trimester of pregnancy induced a unique humoral and cellular response at delivery. Conclusion SARS-CoV-2 infection closer to delivery could incline to adverse pregnancy outcomes. Therefore, the utmost care is required for SARS-CoV-2 infected pregnant women and their newborns. Trial registration The study protocol was approved by the Institutional Review Board of the First Hospital of Jilin University with the approval code number 23K170-001, and informed consent was obtained from all enrolled patients prior to sample collection.